Synthesis of porous nanoparticles and their use as a cytotoxic agent. - Essa, Hayder J. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: In this study, a targeted drug delivery system has been developed based on nanoporous particles covered with cadmium sulfide and loaded with 5-flourouracil. The nanoparticles loaded drug exerts a cooperative antineoplastic activity. Results: The development of nanoparticles loaded anticancer agent for possible application in targeted treatment of cancer where the drug release is triggered by externally applied UV irradiation. In addition, the treatment of cancer cells with drug loaded magnetic material leads to a decrease in viability of the cells due to the activity of cadmium nanoparticles. Upon exposure to low power UV light (365 nm) the loaded 5-flourouracil is released which induces additional decrease in viability of Cervical carcinoma cells HeLa. Methods: Iron oxide nanoparticlers were synthesized and functionalized with cadmium and loaded with 5-flourouracil. Different techniques were used for characterization such as infrared (IR) and ultraviolet (UV) measurements. A cell culture test was done in order to investigate the effect of drug loaded on nanoparticles. Conclusions: In summary, an anticancer drug delivery system based on nanoporous material loaded 5-fluorouracil has been developed. The cooperative anticancer effect of nanoparticles and loaded 5-flourouracil was observed.